PERSONAL FACTORS, RELIABILITY FACTORS DALAM PEMANFAATAN ATAS ADOPSI E-GOVERNMENT: Peranan Intention To Use - Rachmawati, Rachma (2021)
E-Government as a system of digital interaction between a government and other parties, such as citizents and business sector. However, e-Government systems have been plagued by and unsatisfactory, or even a decreasing, level of trust among other parties. The research attempts to bridge this gap, by examining the factors affecting adoption and utilisation of e-Government within the indirectly effect of intention to use. The aims of study is to examine and prove empirically the affecting personal factors and reliability factors on adoption and utilisation of e-Government indirectly through by intention to use. The populaion of this study is 103 government employees, 36 citizens, and 19 participants from the business sector in Provincial Government of DKI Jakarta. The reliability and the validity of the questionnaire have been thoroughly examined, while the Structural Equation Modeling (SEM) technique has been used to analyze the data. The results indicate that personal factors and perceived trust significantly affect adoption and utilisation of e-Government, reliabilty factors signinicantly affect intention to use, and intention to use does not mediate the effect between personal factors, reliability factors, and adoption utilisation of e-Government.